2020
DOI: 10.1002/adfm.201908963
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx‐Like Hydrogel Coatings for Small Diameter Vascular Grafts

Abstract: Novel biological vascular conduits, such as decellularized tissue engineered vascular grafts (TEVGs) are hindered by high thrombogenicity. To mimic the antithrombogenic surface of native vessels with a continuous glycosaminoglycan layer that is present on endothelial cells (ECs), a hyaluronic acid (HA) modified surface is established, to effectively shield blood platelets from collagen‐triggered activation. Using the amine groups present on 4 mm diameter decellularized TEVGs, a continuous HA hydrogel coating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Flow rate in the bioreactor was set to 10 mL/min to mimic abdominal aortic flow in a rat. 72 Glucose tolerance testing demonstrated that BVPs in flowing bioreactors trended higher in insulin release at later time points, perhaps due to the convective properties associated with the bioreactor setup, including increased oxygen delivery and removal of secreted insulin. Quantitatively, a rat-sized BVP in the flow bioreactor could secrete approximately 25 μg of insulin in 2 h. Given that a rat requires approximately 3–4 IU (102–136 μg) of insulin per day to maintain normoglycemia, the bioreactor studies showed that the rat-sized BVP should secrete enough sufficient insulin to meet rat daily requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Flow rate in the bioreactor was set to 10 mL/min to mimic abdominal aortic flow in a rat. 72 Glucose tolerance testing demonstrated that BVPs in flowing bioreactors trended higher in insulin release at later time points, perhaps due to the convective properties associated with the bioreactor setup, including increased oxygen delivery and removal of secreted insulin. Quantitatively, a rat-sized BVP in the flow bioreactor could secrete approximately 25 μg of insulin in 2 h. Given that a rat requires approximately 3–4 IU (102–136 μg) of insulin per day to maintain normoglycemia, the bioreactor studies showed that the rat-sized BVP should secrete enough sufficient insulin to meet rat daily requirements.…”
Section: Resultsmentioning
confidence: 99%
“…The interstitial space surrounding the outside of the coated conduit was set to 40 mmHg 31 . Inlet flow velocity through the lumen of the graft was set to 27 cm/s for rat TVCs 32 and 0.9 m/s for human TVCs 33 . The O 2 diffusion coefficients for decellularized vessels and fibrin were 1.25 × 10 −9 m 2 /s 34 and 1.7 × 10 −9 m 2 /s 35 respectively.…”
Section: Methodsmentioning
confidence: 99%
“… 150 , 151 In another attempt to mimic the endothelium that protects the vessel wall from the platelet attachment, a glycocalyx-like hyaluronic acid coating on the decellularized TEVG lumen reduced thrombus formation. 152 Other approaches to prevent thrombosis in small-caliber grafts include in situ endothelial seeding into the graft lumen, 153 coating of the lumen with agents to promote endothelialization via circulating endothelial progenitor cells or migrating ECs from the anastomosis regions, 154 and coimmobilization of the ACH11 antithrombotic peptide and CAG cell-adhesive peptide to prevent platelet activation and facilitate EC adhesion at the same time (Figure 3 ). 155 In addition to direct coating of these substances onto the graft lumen, local delivery of therapeutic genetic material also has the potential to prevent intimal hyperplasia and stenosis.…”
Section: Current and Future Research Avenuesmentioning
confidence: 99%